Fluctuations and ion-acoustic waves in collisional dusty plasma with variable grain charge - Momot, A.I.; Zagorodny, A.G.; Momot, O.V. (Вопросы атомной науки и техники, 2018)
The kinetic theory of electric fluctuations in a collisional weakly ionized dusty plasma is formulated with regard to the grain charg variations. The spectra of ion-acoustic wave and of electron density correlation in nonisothermal plasmas are calculated for various values of grain density and grain size.